2017
DOI: 10.1186/s12934-017-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct expression of active human tissue inhibitors of metalloproteinases by periplasmic secretion in Escherichia coli

Abstract: BackgroundAs regulators of multifunctional metalloproteinases including MMP, ADAM and ADAMTS families, tissue inhibitors of metalloproteinases (TIMPs) play a pivotal role in extracellular matrix remodeling, which is involved in a wide variety of physiological processes. Since abnormal metalloproteinase activities are related to numerous diseases such as arthritis, cancer, atherosclerosis, and neurological disorders, TIMPs and their engineered mutants hold therapeutic potential and thus have been extensively st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Using protease deficient host BL21 reduced the amount of unwanted truncations. In addition, although cdMMPs do not have disulfide bonds, we found that co-expression of molecular chaperon DsbC (a disulfide isomerase) significantly improved the yields of cdMMPs (Fig 2B), a similar observation for TIMPs [15]. …”
supporting
confidence: 62%
“…Using protease deficient host BL21 reduced the amount of unwanted truncations. In addition, although cdMMPs do not have disulfide bonds, we found that co-expression of molecular chaperon DsbC (a disulfide isomerase) significantly improved the yields of cdMMPs (Fig 2B), a similar observation for TIMPs [15]. …”
supporting
confidence: 62%
“…N‐terminal domain of TIMP‐2 (nTIMP‐2) was prepared from periplasmic expression . Purified cdMMP‐14 was biotinylated by using EZ‐Link Sulfo‐NHS‐LC kit (Thermo Fisher).…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, the prokaryotic cytosol is reductive and incompatible with disulfide bond formation that occurs in the oxidative endoplasmic reticulum of eukaryotes. Currently, no holistic prokaryotic expression strategy to produce uniformly labeled mammalian glycoproteins exists, though multiple groups are engineering E. coli to surmount this limitation (Lee, Nam, Nuhn, Wang, Schneider, & Ge, 2017; Schein et al, 1992; Valderrama-Rincon et al, 2012; Wang & Amin, 2014). Eukaryotic microbes, namely the yeasts, have an analogous oxidative secretory system with glycosylation machinery.…”
Section: Glycoprotein Productionmentioning
confidence: 99%